Hydrochemical analysis of a basin under anthropogenic influence and effects in Manaus’ shoreline, Central Amazonia - CALVO, Bruno Del Rio (2020)
Environmental research realized at Educandosbasin (Manaus –AM), which includes several dwelling-places and Manaus Free Trade Zone (ZFM), to avail the impact of anthropogenic activity on local streams and potential influences over Rio Negro, at Manaus’ shoreline.It was determined pH, E.C., turbidity, temperature, TSS, anions (HCO3-, NO3-, F-, Cl-, SO42-) and dissolved metals (Ni2+, Pb2+, Cr3+, Cu2+, Fe2+, V+, Zn2+e Al3+). Anions were measured by HPLC; metals, by ICP-OES; and remainder parameters by classic methods. All theanalyzed parameters were altered at streams because of anthropogenic activity. Results showed Quarenta stream hadn’t had altered the quality standards of Rio Negro’s water. It was noticed a high degradation on the base level of Cachoeirinha and Mestre Chicostreams, in which were found the highest levels of Cl-, F-, SO42-, E.C., pH e HCO3-. These parameters were higher than those obtained in last decades, indicating an increase in contamination by sewage. Places near ZFM presented high levels of Ni2+e Al3+,arising from industrial waste. Levels for metals Pb2+, Cr3+, Cu2+, V+were recorded below the permissible limits according to Resolution n.357/2005 –CONAMA in all spots, indicating a possible reduction on the emission of potentially toxic metals.